Aporías de las memorias literarias (2007)
Black back of time (1998), by the Spanish novelist Javier Marías, as "literary memories" of All Souls (1989), clashes with the aporia of the autobiographical relationship of past events. Thus the metaphorical nature of the discourse, that is, its inescapa